Structural effects of ditopic azoprobe–cyclodextrin complexes on the selectivity of guest-induced supramolecular chirality. Issue 90 (17th October 2018) - Fujiwara, Shoji; Nonaka, Kentaro; Yamaguchi, Mai; Hashimoto, Takeshi; Hayashita, Takashi
Abstract : Guest-induced supramolecular chirality: the guest ion selectivity was dramatically altered by a slight change in the spacer length of (15C5-Azo- n -dpa )2 –γ-CyD complexes in water. Abstract : Benzo-15-crown-5 and dipicolylamine are contained as the binding sites in a ditopic azoprobe (15C5-Azo- n -dpa ). However, the selectivities of guest-induced supramolecular chirality for cations and anions were dramatically altered by a slight change in the spacer length of (15C5-Azo- n -dpa )2 –γ-CyD complexes in water.